2006
DOI: 10.1111/j.1365-313x.2005.02624.x
|View full text |Cite
|
Sign up to set email alerts
|

Rice plants take up iron as an Fe3+‐phytosiderophore and as Fe2+

Abstract: SummaryOnly graminaceous monocots possess the Strategy II iron (Fe)-uptake system in which Fe is absorbed by roots as an Fe 3þ -phytosiderophore. In spite of being a Strategy II plant, however, rice (Oryza sativa) contains the previously identified Fe 2þ transporter OsIRT1. In this study, we isolated the OsIRT2 gene from rice, which is highly homologous to OsIRT1. Real-time PCR analysis revealed that OsIRT1 and OsIRT2 are expressed predominantly in roots, and these transporters are induced by low-Fe conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
620
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(640 citation statements)
references
References 54 publications
11
620
1
8
Order By: Relevance
“…This represents a major difference between Os BOR1 and At BOR1. There are several reports of nutrient transporter genes that are induced by the nutrient conditions, including the rice genes AMT1;2 (Sonoda et al, 2003) and IRT1 (Ishimaru et al, 2006) and the Arabidopsis genes YSL2 (Schaaf et al, 2005) and the AMTs (for review, see Loque and von Wiré n, 2004), but in these cases, no changes in cell-type specific patterns of expression were reported.…”
Section: Changes In the Cell-type Specificity Of Os Bor1 Expression Imentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a major difference between Os BOR1 and At BOR1. There are several reports of nutrient transporter genes that are induced by the nutrient conditions, including the rice genes AMT1;2 (Sonoda et al, 2003) and IRT1 (Ishimaru et al, 2006) and the Arabidopsis genes YSL2 (Schaaf et al, 2005) and the AMTs (for review, see Loque and von Wiré n, 2004), but in these cases, no changes in cell-type specific patterns of expression were reported.…”
Section: Changes In the Cell-type Specificity Of Os Bor1 Expression Imentioning
confidence: 99%
“…Therefore, it is important to regulate B transport in response to B conditions in the environment, as with other essential nutrients. For example, major transporters in plants, such as the ammonium transporters (AMTs) (Loque and von Wiré n, 2004) and iron transporters (Ishimaru et al, 2006) are regulated at the transcriptional level and respond to the status of the corresponding nutrient. The iron transporter gene At IRT1 is regulated at both transcriptional and posttranscriptional levels (Connolly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Under Fe-deficient conditions, PS s secretion into the rhizosphere and biosynthesis of Ps s in plant tissues are markedly increased (Nagasaka et al 2009), with positive effect in the PS s -mediated Femobilization process in the rhizosphere. It is interesting to note that rice, a strategy II plant releasing PS s (2′-deoxymugineic acid [DMA]) and taking up the entire Fe III -PS complexes, is also able to take up directly Fe II from the soil solution, definitely an advantage when rice is cultivated in submerged conditions (Ishimaru et al 2006). On the contrary, it has been recently demonstrated that a Fe III complex with DMA, a PS s released by maize roots, could be absorbed directly by roots of a neighboring dicot using a transporter codified by a gene belonging to the yellow stripe1-like (YSL) family and located at the root epidermis (Xiong et al 2013), representing a valid opportunity in Fe acquisition process of dicots when intercropped with monocots.…”
mentioning
confidence: 99%
“…Under low-iron conditions, grasses such as rice (Oryza sativa) and maize (Zea mays) primarily utilize the Strategy II response, whereby they release phytosiderophores into the rhizosphere that bind to ferric iron with high affinity. Phytosiderophore-ferric iron complexes are transported into the root via membrane-localized yellow stripe and yellow stripe-like (YSL) transporters (Curie et al, 2001;Inoue et al, 2009), although several studies suggest that rice is also able to directly uptake ferrous iron (Ishimaru et al, 2006;Cheng et al, 2007).…”
mentioning
confidence: 99%